1997
DOI: 10.1029/97jb01167
|View full text |Cite
|
Sign up to set email alerts
|

On the importance of normal vibrations in modeling of stick slip in rock sliding

Abstract: Abstract. In this paper, numerical studies of friction-induced dynamic instabilities,in particular, stick-slip sliding of rocks, are presented. Of special interest is the importance of normal compliance of the interface and associated normal vibrations in the occurrence of dynamic instabilities. To clearly illustrate this importance, the interface is represented by the Oden-Martins constitutive model which does not exhibit explicit velocity or slip dependence of friction. This friction model is utilized in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Figure 3 shows a typical trajectory of the friction stress in slip and slip rate space. We choose to specify the friction explicitly in terms of stresses and independent of the fault normal stress, because dynamic changes in friction during slip may be independent of the overburden pressure as a result of dynamic processes [see, e.g., Brune et al , 1993; Melosh , 1996; Tworzydlo and Hamzeh , 1997; Brodsky and Kanamori , 2001].…”
Section: Methodsmentioning
confidence: 99%
“…Figure 3 shows a typical trajectory of the friction stress in slip and slip rate space. We choose to specify the friction explicitly in terms of stresses and independent of the fault normal stress, because dynamic changes in friction during slip may be independent of the overburden pressure as a result of dynamic processes [see, e.g., Brune et al , 1993; Melosh , 1996; Tworzydlo and Hamzeh , 1997; Brodsky and Kanamori , 2001].…”
Section: Methodsmentioning
confidence: 99%
“…Whereas the friction models and the variation of the parameters with the material properties and the depth are not based on a particular mechanism for the sliding friction, a number of mechanisms have been proposed for low levels of dynamic friction during earthquakes (Brune et al, 1993;Melosh, 1996;Harris and Day, 1997;Sleep, 1997;Tworzydlo and Hamzeh, 1997;Ben-Zion and Andrews, 1998;Anooshehpoor and Brune, 1999;Brodsky and Kanamori, 2001). A combination of such mechanisms may produce a complex variation in the effective coefficient of friction over the depth of the fault during sliding, which resembles our ad hoc variation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, stateand rate-dependent friction models imply high-sliding friction in the presence of large fault normal compressive stresses. Several plausible mechanisms have been suggested to explain why friction varies in both space and time during earthquakes for dynamic reasons, for example, wrinklelike slip pulses associated with a contrast in material properties (Harris and Day, 1997;Ben-Zion and Andrews, 1998;Anooshehpoor and Brune, 1999), acoustic fluidization (Melosh, 1996), normal vibrations (Brune et al, 1993;Tworzydlo and Hamzeh, 1997), and elastohydrodynamic lubrication (Brodsky and Kanamori, 2001). Instead of choosing to model any particular mechanism, we approximate the general features of the behaviors with simple friction models because several of these mechanisms may be combining to change the friction stress during sliding.…”
Section: Friction Modelsmentioning
confidence: 99%
“… Bureau et al [2000] and Cochard et al [2003] studied the effect of high frequency normal load vibrations and found that even a modest modulation induced substantial frictional weakening. Tworzydlo and Hamzeh [1997] noted that the inclusion of normal force vibrations in models of rock friction can cause instability. Theoretically, Perfettini et al [2001] identified a resonant response of shear zone strength, involving strong amplification of the shear stress and velocity response for a small range of friction parameters and a critical loading stiffness.…”
Section: Introductionmentioning
confidence: 99%